A conceptual framework of blended learning for self-directed learners in the social context: case of mobile learning / Wan Abdul Rahim Wan Mohd Isa, Zulinda Ayu Zulkipli and Mimi Nurakmal Mustapa - Wan Mohd Isa, Wan Abdul Rahim; Zulkipli, Zulinda Ayu; Mustapa, Mimi Nurakmal (UiTM Press, 2017)
Currently, the factors for adopting m-learning revolve around higher education settings. However, the factors surrounding different cultural and background context of the user in using m-learning in different contexts are not fully explored, especially in the social context. Thus, there are needs to understand blended learning for self-directed learners from different communities. The main objectives of this paper are (i) to develop a conceptual framework of blended learning for self-directed learners in the social context by using mobile learning as the case study and (ii) to provide recommendations for improving m-learning for self-directed learners. The adapted conceptual framework which consists of (i) learner aspects, (ii) device aspects and (iii) the social aspects, was used in this study. A survey was conducted with 190 respondents who have experience in using mobile devices for self-directed learning and their qualitative responses were recorded. The preliminary descriptive results are presented to understand the user's background and qualitative responses in supporting the recommendations related to (i) learner's aspects, (ii) device aspects and (iii) the social aspects, as suggested in the conceptual framework.